Dampak Culture shock terhadap Motivasi Belajar dalam Pembelajaran BIPA - Indra; Emy Rizta Kusuma (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2026)
This study aims to describe the forms of culture shock experienced by learners of Indonesian as a Foreign Language (BIPA) and to analyze its impact on their learning motivation. The background of this study arises from the increasing interest of international students in learning Indonesian, which simultaneously brings challenges as they enter new social, academic, and cultural environments. Culture shock becomes an inevitable phenomenon, particularly when learners encounter values, habits, and communication styles that differ significantly from those of their home countries. In this context, the process of learning a new language cannot be separated from cultural adaptation, which plays an essential role in determining the success of language acquisition. This research employs a qualitative descriptive method with data collected through semi-structured interviews involving two foreign students at Universitas Trunojoyo Madura. The data were analyzed using Sugiyono’s interactive analysis model, which includes data reduction, data display, and conclusion drawing. Language barriers emerged as the most dominant factor influencing learning motivation, as they disrupted the fulfillment of basic psychological needs in Self-Determination Theory namely autonomy, competence, and relatedness. However, as the learners progressed into the recovery and adjustment phases, their motivation increased in line with improved language skills and social interaction. This study underscores the importance of cultural adaptation support in BIPA learning environments.